Clinical and genetic parallels in congenital brain lesions without epilepsy - P. L. Sokolov; A. G. Prityko; N. V. Chebanenko; P. A. Romanov (Русский журнал детской неврологии)
Background. The problem of preventing the development of gross congenital brain lesions and their successful treatment is more than relevant now. It is known that approximately in every third case of the development of congenital cerebral palsy (CP), it is impossible to identify the main pathogenetic factor. This determines the activity of the search for gene mechanisms for the formation of this phenotype. G. McMichael et al. were among the first to identify the most relevant directions of the influence of genes on the formation of the CP phenotype.Objective: to study the influence of gene determinants on the formation of the phenotype of CP, which is not accompanied by epilepsy.Materials and methods. Gene abnormalities in 18 patients with CP were divided into groups of determinable physiological processes. Genetic mutations were confirmed by next generation sequencing (NGS) and Sanger trio methods. For the study, samples of the patients' venous blood were taken.Results and discussion. The analysis showed that genes from different groups by determinants are to varying degrees associated with the formation of the CP phenotype. The “map of determinants” in the pathogenesis of CP is specific. The pathogenesis involves genetically determined disorders of cell division and neuroontogenesis (neuronal migration, sprouting, myelination, partly apoptosis), cell metabolism, including those whose disturbance leads to the formation of storage diseases, transmembrane transport, the exchange of neurotransmitters and the functioning of synapses, the formation of and the functioning of the cytoskeleton, as well as the regulation of immunity and oncogenesis. Malformations of the brain are more often associated with determinants of the regulation of the formation and functioning of the cytoskeleton, neuroontogenesis, as well as the processes of cell division (chromatin modification, transcription, replication). The pathogenesis of congenital cerebral palsy does not involve (according to our data) the determinants of canalopathy, energy supply of the cell, intracellular synthesis with the Golgi complex, and ribosomal synthesis.Conclusions. Genetically determined CP is a universal phenotype that implements the multidirectional effect of the genome. The influence of the genome does not apply to the energy supply of the cell, ribosomal synthesis and the functioning of the Golgi complex. In the absence of epilepsy in the phenotype, there is no influence of the genes of canalopathies.